Elements of differential equations in the mathematics course for students of economics - Biernacki, Marek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
The article presents a proposal of one lecture with elements of differential equations included in a 30-hour course in mathematics for students of economics at the University of Economics in Wrocław. The author puts forward a presentation of some basic methods for solving first order differential equations exemplified by two macroeconomic growth models: the Domar model and the Solow model.
Didactics of Mathematics, 2015, Nr 12 (16), s. 5-10
Keywords: elements of economic equations; models of economic growth; differential equations